Effective ﻿nanoparticulate-type encapsulation delivery system for hydrophilic proteins and peptides - Flavio Massignan; Gergő Gyulai; Kata Horváti; Szilvia Bősze; Éva Kiss (eXPRESS Polymer Letters, 2024)
The elaboration of potent delivery systems for peptides/proteins is still a challenge but is increasingly needed in advanced therapy. In the present research, we have developed a nanoencapsulation system for peptides/proteins, which is suitable for the delivery of hydrophilic bioactive compounds. The preparation method combines the advantageous properties of reverse nanoemulsion and nanoprecipitation, resulting in the formation of nanoparticles in the size range of 350–500 nm. The polymeric coating composed of polycaprolactone allows chemical functionalization and protection while the inner microenvironment (containing 1-decanoyl-rac-glycerol and N,N-dimethyldodecylamine N-oxide surfactants) provides aqueous surrounding for the active with structural fidelity. Hen egg white lysozyme and β-lactoglobulin were successfully encapsulated, achieving protein contents of 10–60 μg/mg and encapsulation efficiencies ranging from 5–50% depending on the protein type and loading concentration. In vitro release measurement showed a biphasic sustained release profile of both proteins in the time range of one month. In vitro cytotoxicity investigation of protein-loaded nanoparticles exhibited good cell viability (above 95% at the highest treatment concentration of 0.3 mg/ml). The encapsulated membrane-active peptides have shown improved bioactivity.